Високочастотні плазмові розряди в пробкотронах і стелараторах - Моісеєнко, Володимир Євгенович; Moiseenko, Volodymyr E. (Харків : Харківський національний університет імені В.Н. Каразіна, 2021)
Moiseenko V.E. Radio-frequency plasma discharges in fusion devices. - Qualifying scientific work in the form of manuscript. The thesis on a scientific degree of the doctor of physical and mathematical sciences, specialty 01.04.08 – plasma physics. – National Research Center "Kharkiv Institute of Physics and Technology"; V. N. Karazin Kharkiv National University of the Ministry of Education and Science of Ukraine. – Kharkiv, 2021. A new numerically stable method of weighted residuals and a model for Maxwell's equations in cylindrical geometry are developed, where all components of the electric field are represented by means of identical finite elements. It is more effective than Galerkin method when stiffness takes place in Maxwell's equations. An original numerically stable model for the calculation of electromagnetic fields in the plasma of axisymmetric open traps without taking into account slow waves has been developed. It is implemented in the new upgraded PLFEM-S code, which differs in the possibility of numerically stable calculation of azimuthal-asymmetric modes. The new method is proposed, and the model for calculation of electromagnetic fields in plasma of non-axisymmetric open traps without taking into account slow waves is developed. A new numerical model for calculating the distribution and absorption of radio frequency fields by sloshing ions (splashing ions). An original and effective method for calculations with strongly oscillating solutions has been developed. It allows one to use a sparse grid and thereby significantly reduce computational costs.
Radio-frequency plasma discharges in fusion devices
Розроблена низка нових чисельно стійких методів для рівнянь Максвелла: метод зважених нев'язок і модель у циліндричній геометрії, варіант методу шахової сітки для осесиметричних відкритих пасток, новітній метод скінченних різниць для двовимірно неоднорідної плазми. Представлені моделі на базі цих методів. Розроблений оригінальний і ефективний метод для розрахунків із сильно осцилюючими розв’язками. Наведена методика застосування методу штрафів щодо шарів нижнього гібридного резонансу в холодній плазмі. Запропонована нова форма рівнянь Максвела для числового моделювання. Розраховані ефективні сценарії високочастотного нагрівання іонів, що плещуться, у відкритій пастці. Наданий детальний аналіз винайденого сценарію швидкого нагрівання плазми в пробкотроні під час її створення. Зроблене теоретичне дослідження проникнення електростатичного поля через Фарадеїв екран.
Keywords: високочастотне нагрівання плазми; рівняння Максвелла; метод Галеркіна; створення плазми; кондиціонування стінок; термоядерно-ядерний гібрид; radio-frequency plasma heating; Maxwell’s equations; Galerkin method; plasma production; wall conditioning; fusion-fission hybrid